Runaway History and Past 30‐Day Opioid Misuse in Justice‐Involved Adolescents. (23rd August 2021) - Johnson, Micah E.; Lloyd, Shawnta L.; Bristol, Skye C.; Rosel, Giselle; Otufowora, Ayodeji A.; Epps, Nathan N.
ABSTRACT: This study used a sample from the Florida Department of Juvenile Justice (n= 79, 960) to analyze the association between runaway history and past 30‐day opioid misuse (OM) among justice involved adolescents. Past 30‐day OM was confirmed using a urine analysis. Adolescents who were runaways in their lifetime were twice as likely to misuse opioids, and those who were runaways at the time of arrest were three times as likely to be opioid misusers compared to adolescents who never ran away or been kicked out of a home. These findings emphasize a need for resources that focus on developing strong attachment bonds.